2016
DOI: 10.1097/cji.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cytokine-activated NK Cells for Use in Adoptive Cell Therapy in Cancer Patients

Abstract: Cell-based immunotherapy using donor-derived natural killer (NK) cells after allogeneic hematopoietic stem cell transplantation may be an attractive treatment of residual leukemia. This study aimed to optimize clinical grade production of a cytokine-activated NK-cell product. NK cells were isolated either by double depletion (CD3(-), CD19(-)) or by sequential depletion and enrichment (CD3(-,) CD56(+)) via CliniMACS from leukapheresis material and cultured in vitro with interleukin (IL)-2 or IL-15. Both NK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 65 publications
4
22
0
1
Order By: Relevance
“…For repeated NK cell applications, we tested continuously expanded cells and compared their cytotoxicity to that of cryopreserved cells. In line with reports on IL-15-stimulated NK cells (75), in our study, we observed a reduced cytotoxic capacity of cryopreserved cytokine-stimulated compared to continuously expanded NK cells (Figure S3A in Supplementary Material) and therefore performed analysis with the latter if several rounds of NK cell application were necessary. Another advantage of NK cell expansion using a feeder cell free IL-15 + 21 boost protocol will be that it easily fulfils the GMP criteria required for clinical application.…”
Section: Discussionsupporting
confidence: 90%
“…For repeated NK cell applications, we tested continuously expanded cells and compared their cytotoxicity to that of cryopreserved cells. In line with reports on IL-15-stimulated NK cells (75), in our study, we observed a reduced cytotoxic capacity of cryopreserved cytokine-stimulated compared to continuously expanded NK cells (Figure S3A in Supplementary Material) and therefore performed analysis with the latter if several rounds of NK cell application were necessary. Another advantage of NK cell expansion using a feeder cell free IL-15 + 21 boost protocol will be that it easily fulfils the GMP criteria required for clinical application.…”
Section: Discussionsupporting
confidence: 90%
“…Also, it has been recently shown that combination of IL‐2 and IL‐21 can increase this proportion to even greater extent . IL‐2 and other cytokines, such as IL‐15, IL‐21, are important tools in studying NK cells, as they allow maintaining the viability and growth of the cells in culture up to several weeks . This response to cytokines is widely used to expand NK cells ex vivo for their further applications in adoptive immunotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…15 IL-2 and other cytokines, such as IL-15, IL-21, are important tools in studying NK cells, as they allow maintaining the viability and growth of the cells in culture up to several weeks. [16][17][18] This response to cytokines is widely used to expand NK cells ex vivo for their further applications in adoptive immunotherapy. [19][20][21] For this purpose, soluble cytokines can be used, but much more impressive results have been acquired using feeder cells (K562, EBV cell lines), modified to express membrane-bound cytokines and other activating molecules, such as 4-1BBL and MICA, 20 mbIL-15 and 4-1BBL.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, compared with T cells and many other human cells, NK cells are more sensitive to freezing and thawing, especially when they have been activated by cytokines. In addition to the variable survival rate during thawing, the cytotoxicity of NK cells decreased significantly after thawing [42]. Also, cytokine-activated NK cells are very sensitive to lower temperatures [43].…”
Section: Storage and Shipping Of Nk Cell Productsmentioning
confidence: 99%